Undrained triaxial compression tests on three-dimensional reinforced sand: effect of the geocell height. Issue 5 (31st March 2022) - Benessalah, Ismail; Sadek, Marwan; Villard, Pascal; Arab, Ahmed
Abstract: This paper presents an experimental thorough study on geocell reinforced loose sand (Dr = 25%), focusing on the improvement of the shear strength in undrained conditions. The experimental program includes a series of undrained compressive tests (CU) performed on loose sand samples with and without reinforcement. The experimental tests are performed for various geocell height (Hg = 15, 25 and 35 mm) and at different level of effective confining pressure (σ'c = 50, 100 and 200 kPa). The obtained results show a significant effect of geocells height and initial confining pressure on the shear strength of the reinforced sand. The apparent cohesion of the reinforced soil increases linearly with the axial strain while the friction angle is rather constant and slightly dependent on the sample deformation.